Targeting Integrin-Dependent Adhesion and Signaling with 3-Arylquinoline and 3-Aryl-2-Quinolone Derivatives: A new Class of Integrin Antagonists - Fiorucci, Sandrine (PLoS One, 2015)
We previously reported the anti-migratory function of 3-aryl-2-quinolone derivatives, chemically close to flavonoids (Joseph et al., 2002). Herein we show that 3-arylquinoline or 3-aryl-2-quinolone derivatives disrupt cell adhesion in a dose dependent and reversible manner yet antagonized by artificial integrin activation such as manganese. Relying on this anti-adhesive activity, a Structure-Activity Relationship (SAR) study was established on 20 different compounds to throw the bases of future optimization strategies. Active drugs efficiently inhibit platelet spreading, aggregation, and clot retraction, processes that rely on α(llb)β(3) integrin activation and clustering. In vitro these derivatives interfere with β(3) cytoplasmic tail interaction with kindlin-2 in pulldown assays albeit little effect was observed with pure proteins suggesting that the drugs may block an alternative integrin activation process that may not be directly related to kindlin recruitment. Ex vivo, these drugs blunt integrin signaling assayed using focal adhesion kinase auto-phosphorylation as a read-out. Hence, 3-arylquinoline and 3-aryl-2-quinolone series are a novel class of integrin activation and signaling antagonists.